2005
DOI: 10.4049/jimmunol.175.4.2684
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Extract Suppresses Human Dendritic Cell Function Leading to Preferential Induction of Th-2 Priming

Abstract: Dendritic cells (DC) are key regulators of immune responses. In the current study, we hypothesized that cigarette smoke-induced aberrance in DC function is an important mechanism by which smokers develop cancer, infection, and allergy—diseases common in smokers. We demonstrate that cigarette smoke extract (CSE) inhibits DC-mediated priming of T cells, specifically inhibiting the secretion of IFN-γ whereas enhancing the production of IL-4 in the MLR. Conditioning with CSE did not effect cytokine (IL-10, IL-6, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
170
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 188 publications
(189 citation statements)
references
References 61 publications
15
170
1
3
Order By: Relevance
“…Aqueous CSE was prepared from Kentucky research cigarettes 1RF4 as recently described (Vassallo et al, 2005). The nicotine levels in the CSE preparations were measured in the institutional clinical laboratory using liquid chromatography-tandem mass spectrometry: the mean nicotine content in 4 separate samples of 100% CSE was 21,460±2778 ng/ml.…”
Section: Generation Of Cigarette Smoke Extract (Cse)mentioning
confidence: 99%
See 4 more Smart Citations
“…Aqueous CSE was prepared from Kentucky research cigarettes 1RF4 as recently described (Vassallo et al, 2005). The nicotine levels in the CSE preparations were measured in the institutional clinical laboratory using liquid chromatography-tandem mass spectrometry: the mean nicotine content in 4 separate samples of 100% CSE was 21,460±2778 ng/ml.…”
Section: Generation Of Cigarette Smoke Extract (Cse)mentioning
confidence: 99%
“…The final concentration of CSE used in the experiments described was 1-2% -final nicotine concentration in vitro of 1% CSE was equal to 214.6±27.8 ng/ml. The concentrations of <3% were chosen because of preliminary viability studies that demonstrated a lack of nonspecific toxicity and >95% viability compared with controls, as determined by the XTT assay and AnnexinV/propridium iodide staining with these CSE preparations (Vassallo et al, 2005).…”
Section: Generation Of Cigarette Smoke Extract (Cse)mentioning
confidence: 99%
See 3 more Smart Citations